The challenges of preserving our modernist public parks - Karlócainé Bakay, Eszter; Takácsné Zajacz Vera, Vera; Gergely, Antal (4D Journal of Landscape Architecture and Garden Art, 2023)
Among the projects of the 20th century modern landscape architecture, there are some works that deserve to be pre-served as an integral part of the garden heritage. A world-wide inventory and evaluation of this landscape heritage is currently underway to identify those works that best represent the landscape architecture of the period. How can these works be restored in a way that meets today's ecological and social sustainability requirements without losing their original character? In the intensively used public parks presented in this article, complete reconstruction is generally not feasible, but the scale of the transformation is a central issue. International experi-ence shows how unclear the criteria for aspects of selecting works to be preserved. For the time being, it is still often a subjective judgement, even within the professional community, whether the intervention used in the renovation process changes the composition of the original work. The renewal of any historic park and garden from any era must address sustainability, usually primarily from an ecological perspective. However, the contemporary regeneration of public parks and urban open spaces from the modern era, which are still intensively used today, is further complicated by the need for contemporary recrea-tional functions to be incorporated during the renovation and the application of universal design principles, which present additional challenges to integrate. Social sustainability is a strong requirement at these renovations.In this article, we analyse four modern public parks that were been renewed in the last 25 years or are in the process revitalization. In our country today, there is still no professional consensus as to which modern public parks can be considered valuable and worth preserving for the future - if not through complete reconstruction, then by carefully preserving the basic concept and compositional principles. The guiding principle in the selection of the public parks presented in this article was that they should be of different periods and have different recreational functions, with different challenges in their restoration.
Keywords: modern public park; composition; concept; ecological and social sustainability; contemporary design principles